Market Price of Risk Analysis from Three Major Industrial Countries on the Stability of the Brennan-Schwartz Model - Handhika, Tri (The Indonesian Capital Market Review, 2012)
At any given time, market price of risk must be the same for all derivatives and it is linked in particular to interest rate. The Brennan-Schwartz model is one of the stochastic differential equations for the interest rate under the risk neutral probability measure. To estimate parameters of this model, it is required that the real data which are collected in the real world in which the distribution of interest rate process is under the actual probability measure. Therefore, parameter estimators are obtained by changing the measure which is determined by the market price of risk. Hence, market price of risk must make the Brennan-Schwartz model becomes stable, which is important to describe resistance of the model to the perturbation in the initial state or parameters of the model. This paper aims to analyze the market price of risk from three major industrial countries: USA, Japan, and Canada. This analysis can be used as a guideline to decide that the interest rate of these three major industrial countries can be modeled as Brennan-Schwartz model.